Regional Trade Flows and Input Output Data for Europe - Olga Ivanova; D'Artis Kancs; Mark Thissen (Economics and Econometrics Research Institute (EERI), 2019)
The Regional Trade Flows and Input output Data for Europe are constructed at the regional NUTS2 level with sectoral NACE2 detail and developed for spatial macroeconomic modelling and social-economic analysis for answering a wide-range of policy questions, including policies related to investments in innovation, human capital, green infrastructure and Sustainable Development Goals. The Regional Trade Flows and Input output Data for Europe are particularly well suited for structural modelling such as spatial computable general equilibrium models, as all data are fully internally consistent. In the Regional Trade Flows and Input output Data all European regions are connected with each other via inter-regional trade flows, input use and output supply in form of regional trade matrices, input output tables and supply-use tables. This data base is result of a joint collaborative effort over a decade of several research institutes across Europe, including the Netherlands Environmental Assessment Agency (PBL), the European Commission (DG JRC) and the University of Groningen (Ivanova, Kancs and Stelder 2009, Thissen et al. 2014, Thissen et al. 2018, Ivanova, Kancs and Thissen 2019). Among others, the new EU Economic Modelling System (EU-EMS) developed within the EU Framework Programme for Research and Innovation makes use of the Regional Trade Flows and Input output Data for Europe.
Keywords: C68; D58; F12; R13; R30; 330; Inter-Regional Trade Flows; Input output Tables; data; Europe; spatial spillovers; SCGE; modelling